Subclinical left ventricular dysfunction in children after hematopoietic stem cell transplantation for severe aplastic anemia: a case control study using speckle tracking echocardiography - Beom Joon Kim; Kyung Pil Moon; Ji-Hong Yoon; Eun-Jung Lee; Jae Young Lee; Seong Koo Kim; Jae Wook Lee; Nack Gyun Chung; Bin Cho; Hack Ki Kim (Korean Pediatric Society, 2016)
PurposeSevere aplastic anemia (SAA), a fatal disease, requires multiple transfusion, immunosuppressive therapy, and finally, hematopoietic stem cell transplantation (HSCT) as the definitive treatment. We hypothesized that iron overloading associated with multiple transfusions and HSCTrelated complications may adversely affect cardiac function. Left ventricular (LV) function was assessed in children after HSCT for SAA.MethodsForty-six consecutive patients with a median age of 9.8 years (range, 1.5-18 years), who received HSCT for SAA and who underwent comprehensive echocardiography before and after HSCT, were included in this study. The data of LV functional parameters obtained using conventional echocardiography, tissue Doppler imaging (TDI), and speckle-tracking echocardiography (STE) were collected from pre- and post-HSCT echocardiography. These data were compared to those of 40 age-matched normal controls.ResultsIn patients, the LV ejection fraction, shortening fraction, end-diastolic dimension, mitral early diastolic E velocity, TDI mitral septal E' velocity, and STE LV longitudinal systolic strain rate (SSR) decreased significantly after HSCT. Compared to normal controls, patients had significantly lower post-HSCT early diastolic E velocity and E/A ratio. On STE, patients had significantly decreased LV deformational parameters including LV longitudinal systolic strain (SS), SSR, and diastolic SR (DSR), and circumferential SS and DSR. Serum ferritin levels showed weak but significant correlations (P<0.05) with LV longitudinal SS and SSR and circumferential SS and DSR.ConclusionSubclinical LV dysfunction is evident in patients after HSCT for SAA, and was associated with increased iron load. Serial monitoring of cardiac function is mandatory in this population.